Recruiting, Protecting, Participating: African Student-Agents and Student-Activists as Actors of the Study abroad Destination of “North-Cyprus” - (:unkn) unknown (My University, 2023)
In recent years, the literature regarding migratory infrastructure has undergone significant expansion, providing a better understanding of the complexity of the mechanisms that facilitate the movement of individuals across borders. The aim of this article is to engage with this literature in order to give greater attention to the participation of migrants themselves in migratory infrastructures. We analyze the involvement of certain international students in the dynamics that influence the arrival of tens of thousands of students, especially from Sub-Saharan Africa, to North-Cyprus since the late 2000s. Two seemingly antagonistic figures coexist: on one hand, the student-agent, acting as a recruiter for the universities; on the other hand, the student-activist who opposes the mercantile excesses of recruitment. The analysis leads us to highlight what these two figures and the students that embody them have in common in terms of practices and trajectories, as well as what makes them crucial intermediaries between students, universities, and local public services.
Keywords: African Research